2021
DOI: 10.1364/ao.417054
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth-tunable THz absorber based on diagonally distributed double-sized VO2 disks

Abstract: Terahertz absorbers combined with phase-changing V O 2 are a class of stealth materials with adjustable absorptance. However, such absorbers still suffer from insufficient absorption bandwidth. We propose a three-layer terahertz (THz) absorber, consisting of an array of diagonally distributed double-sized V O 2 disks on a silica-coated gold film. We find this structure can generate the superposition of three resonant abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Vanadium dioxide (VO 2 ) is a phase change material, a sudden insulator−metal transition (IMT) occurs at a temperature of about 68 °C, resulting in dramatic changes in electromagnetic properties. 50 By the IMT characteristics of VO 2 , the absorption intensity of the nanosystem coupled between the nanostructure and VO 2 can be thermally switched for linearly polarized light 51 and perfect absorption and asymmetric transmission can be thermally switched for circularly polarized light. 52 Hence, the introduction of MoS 2 and VO 2 into our dielectric nanostructures is expected to enhance and dynamically adjust the CD signal of the dielectric nanostructures.…”
Section: T H Imentioning
confidence: 99%
“…Vanadium dioxide (VO 2 ) is a phase change material, a sudden insulator−metal transition (IMT) occurs at a temperature of about 68 °C, resulting in dramatic changes in electromagnetic properties. 50 By the IMT characteristics of VO 2 , the absorption intensity of the nanosystem coupled between the nanostructure and VO 2 can be thermally switched for linearly polarized light 51 and perfect absorption and asymmetric transmission can be thermally switched for circularly polarized light. 52 Hence, the introduction of MoS 2 and VO 2 into our dielectric nanostructures is expected to enhance and dynamically adjust the CD signal of the dielectric nanostructures.…”
Section: T H Imentioning
confidence: 99%
“…[35] The roomtemperature-bonding technique developed here is compatible with high temperature and chemical etching, and is applicable to switchable multifunctional terahertz devices. [47,49,50]…”
Section: Discussionmentioning
confidence: 99%
“…[6] These two factors prevent the simultaneous achievement of orthogonal-polarization modulation and high efficiency, especially in terahertz or higher frequency regions. Although multilayer vanadium-dioxide metasurfaces have been seen as promising for use in efficient multifunctional devices, such as reconfigurable absorbers, [36][37][38][39][40][41][42][43][44][45][46][47][48] reprogrammable wavefront-engineering metasurfaces, [49,50] and devices switchable between quarterand half-wave plates, [51] these proposals have not been realized experimentally, because of the stringent fabrication challenges. Although a few studies have reported experimental realization of multilayer vanadium-dioxide structures for infrared polarization modulation [52] and terahertz asymmetric transmission, [53] they did not focus on orthogonal-polarization modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Checkerboard structures might be helpful for achieving broadband operation [35]. The room-temperature-bonding technique developed here is compatible with high temperature and chemical etching, and is applicable to switchable multifunctional terahertz devices [47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…These two factors prevent the simultaneous achievement of orthogonal-polarization modulation and high efficiency in any frequency region. Although multilayer vanadium-dioxide metasurfaces have been seen as promising for use in efficient multifunctional devices, such as reconfigurable absorbers [36,37,38,39,40,41,42,43,44,45,46,47,48], reprogrammable wavefront-engineering metasurfaces [49,50], and devices switchable between quarter-and half-wave plates [51], these proposals have not been realized experimentally, because of the stringent fabrication challenges. (Although a few studies have reported experimental realization of multilayer vanadium-dioxide structures for infrared polarization modulation [52] and terahertz asymmetric transmission [53], they did not focus on orthogonalpolarization modulation.)…”
Section: Introductionmentioning
confidence: 99%